Management of Plantar Fasciitis through Panchkarma Principles – A Case Study - Kaushik, Annu; Mangal, Gopesh (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Plantar fasciitis (PF) is a prevalent condition caused by repetitive stress on the plantar fascia, a band of tissue connecting the heel bone to the toes. It constitutes about 80% of heel discomfort cases. This condition typically targets middle-aged individuals, impacting both genders equally, with a lifetime prevalence of approximately 10%. Although often self-limiting, the intense pain prompts many to seek medical help. Early intervention and managing risk factors can lead to rapid symptom relief and improved outcomes. Clinical presentations typically involve initial step discomfort and stiffness, which can be correlated to “Vatakantaka” in Ayurvedic terminology. This condition underscores the importance of early recognition and appropriate management to alleviate symptoms and enhance patient outcomes. Vatakantaka manifests as varying degrees of discomfort from mild to severe in the Pada (foot), Parshini (heel), Gulfa (ankle), and Jangha (calf) regions. Despite conventional pain management approaches, it frequently proves refractory, posing significant challenges and impacting the patient’s quality of life and mobility.